ANALISIS PACING DALAM MEMBENTUK SUSPENSE PADA FILM JOKER KARYA TODD PHILLIPS - Persada, Taruna Satria (Institut Seni Indonesia Padangpanjang, 2024)
The Joker movie shows the journey of Arthur Fleck as he slowly turns into the Joker. The researched aspect of this movie is the editing aspect with a focus on pacing techniques in shaping one of the dramatic elements, suspense. This research uses a qualitative method that is presented descriptively based on theories that contain pacing and dramatics.The results of this research prove that pacing has an important role in shaping the dramatic elements of suspense, by withholding information through cutting with three methods, which are: rate of cutting, rate of change or movement within a shot, and rate of overall change. The dramatic pattern of suspense in the Joker movie has three stages, which are before, during, and after, which are related to each other in shaping the dramatic elements of suspense.